PENGETAHUAN IBU TENTANG TEHNIK POSISI MENYUSUI YANG BENAR DI DESA SIGULANG KECAMATAN PADANGSIDIMPUAN TENGGARA TAHUN 2020 - FATIMAH . (JURNAL ILMIAH SIMANTEK, 2021)
The type of this research is descriptive, collecting data obtained through questionnaires, where the sample of 40respondents and sampling done in total sampling under study based on age, education, employment, information sourcesand parity. Data processed with editing, coding, sroring, tabulating, then analyzed and collected in the table followed bydiscussing the results of research with existing literature theory. The results of the study note that the majority of respondentsare less knowledgeable as much as 20 respondents (50%). Based on the age of respondents with less knowledge as manyas 19 respondents (47.5%) at the age of 20-35 years, respondents are knowledgeable enough as 13 respondents (32.5%)with high school education, less knowledgeable respondents as much as 7 respondents (17.5%) based on self-employed,less knowledgeable respondents as much as 10 respondents (25%) based on information sources from electronic media,less knowledgeable respondents as many as 14 respondents (25%) based on skundipara parity. The results of this study arethe majority of respondents are less knowledgeable so it is expected to breastfeeding mothers to increase knowledge orinsight about health, especially about proper breastfeeding positioning techniques can anticipate problems that will occurduring infant development.